2022
DOI: 10.1016/j.isci.2021.103539
|View full text |Cite
|
Sign up to set email alerts
|

Glycine-induced NMDA receptor internalization provides neuroprotection and preserves vasculature following ischemic stroke

Abstract: Summary Ischemic stroke is the second leading cause of death worldwide. Following an ischemic event, neuronal death is triggered by uncontrolled glutamate release leading to overactivation of glutamate sensitive N -methyl- d -aspartate receptor (NMDAR). For gating, NMDARs require not only the binding of glutamate, but also of glycine or a glycine-like compound as a co-agonist. Low glycine doses enhance NMDAR function, whereas high doses trigger glycine-i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Our present results raise the possibility that Src may mediate or regulate the priming or internalization that is seen with GluN1a-containing NMDARs but that is absent with GluN1b-containing receptors [20]. Glycine has been found to be strongly neuroprotective in in vitro [66] and in vivo [67][68][69][70] models of ischemic stroke. A growing body of evidence suggests that neuroprotection is mediated by non-ionotropic NMDAR function [66,67,70] (i.e.…”
Section: (D) Evolutionary Conservation Of Exon 5 and Its Alternative ...mentioning
confidence: 86%
See 1 more Smart Citation
“…Our present results raise the possibility that Src may mediate or regulate the priming or internalization that is seen with GluN1a-containing NMDARs but that is absent with GluN1b-containing receptors [20]. Glycine has been found to be strongly neuroprotective in in vitro [66] and in vivo [67][68][69][70] models of ischemic stroke. A growing body of evidence suggests that neuroprotection is mediated by non-ionotropic NMDAR function [66,67,70] (i.e.…”
Section: (D) Evolutionary Conservation Of Exon 5 and Its Alternative ...mentioning
confidence: 86%
“…Glycine has been found to be strongly neuroprotective in in vitro [66] and in vivo [67][68][69][70] models of ischemic stroke. A growing body of evidence suggests that neuroprotection is mediated by non-ionotropic NMDAR function [66,67,70] (i.e. by glycine-primed NMDAR internalization).…”
Section: (D) Evolutionary Conservation Of Exon 5 and Its Alternative ...mentioning
confidence: 99%
“…Through the miR-19a-3p/AMPK/GSK-3β/HO-1 pathway, glycine ameliorates apoptosis, inflammatory response and dysregulated glucose metabolism in IS ( 45 ). In addition, in vitro experiments showed that low doses of glycine improved NMDAR function, but high doses of glycine induced NMDAR internalization and thus neuroprotective effects in IS ( 46 ). Inositol phosphate metabolism has been shown to be abnormal in a rat stroke model ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glycine is an essential coagonist of NMDARs. Glycine is an essential coagonist of NMDARs [24,25].Glycine accumulation leads to NMDAR hyperactivation. Overactivated NMDARs severely disrupt synaptic plasticity, leading to learning and memory impairment [26].NR2B is one of the subunits of NMDARs, and NR2B-containing NMDARs increase NMDAinduced excitotoxicity [27].Studies have reported that NR2B expression is signi cantly elevated in hippocampal tissues of diabetic rats, which can lead to inhibition of synaptic plasticity [28].…”
Section: Introductionmentioning
confidence: 99%